ESTIMATES OF COILIA DUSSUMIERl POPULATION ALONG THE NORTHWEST COAST OF INDIA USING COHORT ANALYSIS - Fernandez, Irene; Devaraj, M (Indian Journal of Fisheries, 2011)
Cohort analysis for the Coilia ditssumieri stock along the northwest coast (Maharashtra and Gujarat coasts) of India for 1981-1983 indicated annual recruits to be ranging from 5.1 x 10’ to 6.8 x IC (mean = 5.7 x 10’*) and the spawners from 3.1 X 10Â» to 4.2 x 10Â» mean. 3.55 x 10Â«). The annual yield ranged from 16,353 t to 19,610 t (mean - 17,534 t). The fully recruited group of i + year (6 to 11 mon. fish), which was the age at first maturity as well as for maximum exploitation, formed the mainstay of the fishery. The present yield per recruit (Y|R = 3.0 g, for the annual exploitation ratio, E = 0.51 and the age at first capture, tc = 0.6 year) is close to the maximum Y|R of 3.04 g at E â€¢ 0.6; suggesting that only marginal increase in yield is possible by increasing the effort. At the present level of exploitation (51%), the effective fishing effort is about 1,300 trawlers per day (Maharashtra = 740; Gujarat = 560) and about 2,000 dol netters per day (Maharashtra = 1,200; Gujarat = 800) for about 215 fishing days per year. The fishing effort seems to have remained around this level since 1971 obviously because of near-optimum level of yield from nearly all the inshore stocks including that of C. dussumieri.